RESVERATROL: A MULTIFACETED NATURAL COMPOUND WITH THERAPEUTIC POTENTIAL - DEWALKAR, LALIT P. (International Journal of Pharmacy and Pharmaceutical Sciences, 2026)
Resveratrol, a plant-derived polyphenol abundant in grapes, berries, peanuts, and red wine, has been the subject of intense scientific exploration for more than three decades. First associated with the French Paradox, it is now widely studied for its ability to influence multiple biological pathways that underlie chronic disease and aging. Experimental evidence shows that resveratrol reduces oxidative stress, modulates inflammatory cascades, improves mitochondrial function, and regulates cell survival and metabolism. Through these actions, it exerts antioxidant, anti-inflammatory, cardioprotective, anticancer, neuroprotective, antidiabetic, hepatoprotective, antimicrobial, and anti-aging effects. While laboratory and animal studies provide compelling support, outcomes from human trials remain variable, reflecting challenges such as poor bioavailability, rapid metabolism, and differences in study design. Recent innovations including nanoparticle based carriers, synthetic analogs, and synergistic formulations are being developed to enhance its stability and clinical utility. Resveratrol is not a miracle cure, but rather a promising candidate for adjunct therapy, underscoring the potential of natural compounds to complement conventional medicine pending further clinical validation. Its journey underscores the need for rigorous, long-term, and well controlled clinical studies to establish effective doses, safety profiles, and therapeutic applications. By bridging traditional phytotherapy and modern translational science, resveratrol continues to inspire both researchers and clinicians in the search for holistic approaches to health and disease management.